Three-Dimensional Numerical Analysis of Weld Pool in GMAW with Fillet Joint - Jeong, Hunchul; Park, Kyungbae; Baek, Sungjin; Kim, Dong-Yoon; Kang, Moon-Jin; Cho, Jungho (International journal of precision engineering and manufacturing, 2018)
GMA welding is widely used in many different fields such as automotive, shipbuilding and plant industry and its demand is growing day by day because of its high productivity and quality with cost reduction in manufacturing process. Nevertheless, the studies have been reported just a few cases so far due to its difficulties in expressions for the complexity of physical phenomena and in the derivation of the mathematical models. In this research, its complex numerical models including three-dimensional heat flux, arc pressure and electromagnetic force are newly suggested and its validation is proved through the comparison between the experimental and simulation results. Basically, the arc heat flux, arc pressure and Marangoni flow are employed as the boundary conditions. And electromagnetic force and buoyancy are realized as body terms. The governing equations such as the continuity, momentum, VOF and energy equations are adopted as usual simulations. It is, however, that only these equations cannot fulfill all requirements to investigate the behavior of the weld pool in GMA welding. To compensate the insufficient, three-dimensional mathematical model and coordinate transform of arc are newly suggested to reflect the twisted torch angle and arc effective radius change according to the distance from electrode tip. Suggested analysis model is verified through comparison to lap joint fillet GMAW experiment of steel sheets for automotive industry and it shows successful correspondence.